1987
DOI: 10.1172/jci113034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-myc proto-oncogene in normal human lymphocytes. Regulation by transcriptional and posttranscriptional mechanisms.

Abstract: Aberrant expression of the c-myc gene results from nonrandom chromosomal translocations involving the transcriptionally active antigen receptor gene loci, in particular lymphocytic leukemias and lymphomas, and is believed to contribute to the etiology of these neoplasms. In addition to its expression in abnormal lymphocytes, increased accumulation of c-myc mRNA occurs rapidly in normal B-and T-lymphocytes after stimulation with appropriate mitogens. The mechanisms that mediate these mitogeninduced elevations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…For Northern blots, 5 Ag RNA was fractionated on 1.0% agarose gels containing formaldehyde and transferred to nitrocellulose filters. The blots were prehybridized and then sequentially hybridized with the "P-labeled cDNA probes : HIV-1 (a 6.5kb segment of HIV-1 encoding gag/pol/env), human TGF-01 (provided by Dr. R. Derynck, Genentech Inc., South San Francisco, CA) (32), and He7 (provided by Dr. J. Reed, University of Pennsylvania School of Medicine, Philadelphia, PA) (36). The blots were washed twicein 2x SSC, 0.1% SDS for 15 min at room temperature and for 30 min at 65°C in 0.1x SSC, 0.1% SDS.…”
Section: Methodsmentioning
confidence: 99%
“…For Northern blots, 5 Ag RNA was fractionated on 1.0% agarose gels containing formaldehyde and transferred to nitrocellulose filters. The blots were prehybridized and then sequentially hybridized with the "P-labeled cDNA probes : HIV-1 (a 6.5kb segment of HIV-1 encoding gag/pol/env), human TGF-01 (provided by Dr. R. Derynck, Genentech Inc., South San Francisco, CA) (32), and He7 (provided by Dr. J. Reed, University of Pennsylvania School of Medicine, Philadelphia, PA) (36). The blots were washed twicein 2x SSC, 0.1% SDS for 15 min at room temperature and for 30 min at 65°C in 0.1x SSC, 0.1% SDS.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to highly proliferating cell lines and tissues, MYC RNA levels in purified tonsil T and B lymphocytes are barely detectable and steady‐state rates of transcription are extremely low . Not surprisingly, in situ hybridization studies in normal lymphoid tissue have not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…It was recognised many years ago that upregulation of Myc mRNA accompanied T cell activation (Reed et al , 1987 ; Kelly & Siebenlist, 1988 ; Wang et al , 2011a ). More recently, the Immunological Genome Project has mapped the transcriptional profiles of multiple T cell populations and reported high levels of Myc mRNA in immune-activated effector T cells (Best et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of understanding the control of Myc protein levels in T cells was highlighted recently: immune-activated T cells lacking the system L amino acid transporter Slc7a5 upregulate Myc mRNA but fail to express Myc protein and hence have global metabolic defects (Sinclair et al , 2013 ). In this context, many experiments have analysed Myc mRNA in T cells activated pharmacologically with phorbol esters, calcium ionophores and plant lectins (Kelly et al , 1983 ; Reed et al , 1987 , 1988 ; Kelly & Siebenlist, 1988 ), but there is almost no detailed analysis of Myc protein in T cells responding to physiological stimuli. Accordingly, the present study has explored how engagement of the T cell antigen receptor (TCR) with peptide/major histocompatibility complexes (p/MHC) controls Myc expression.…”
Section: Introductionmentioning
confidence: 99%